2021
DOI: 10.15414/jmbfs.3931
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing the Production of Pectinase of Orange Peel Waste by Penicillium Chrysogenum Mf318506 Using Response Surface Methodology in Submerged Fermentation

Abstract: Pectinases find wide application in different industrial applications, e.g., textile, food, tea, paper and pulp, vegetable oil extractions, saccharification of agricultural remains, and in fermented drinks. Three fungal strains were screened for pectinase production. Results indicated that all strains are capable of producing a pectinase enzyme. Penicillium chrysogenum MF318506 showed the highest pectinase activity (0.214 U/ml) on the recommended medium at 30 ◦C at 150 rpm, on 6 days. Different agricultural wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Govindaraji and Vuppu [52] reported the highest pectinase activity of 45.93 U/mL using a novel strain, Streptomyces fumigates cleroticus VIT-SP4, and orange peel as a substrate, which is in concurrence with the present findings. Ahmed and Awad [20], in their research work, found the maximum pectinase activity by Pencillium chrysogenum MF318506 using orange peels as the substrate. The results of the present study were supported by the literature review; hence, SSF (fermentation method) and orange peels (substrate) were taken for further studies.…”
Section: Production Of Pectinase Using Submerged Fermentation and Sol...mentioning
confidence: 97%
See 1 more Smart Citation
“…Govindaraji and Vuppu [52] reported the highest pectinase activity of 45.93 U/mL using a novel strain, Streptomyces fumigates cleroticus VIT-SP4, and orange peel as a substrate, which is in concurrence with the present findings. Ahmed and Awad [20], in their research work, found the maximum pectinase activity by Pencillium chrysogenum MF318506 using orange peels as the substrate. The results of the present study were supported by the literature review; hence, SSF (fermentation method) and orange peels (substrate) were taken for further studies.…”
Section: Production Of Pectinase Using Submerged Fermentation and Sol...mentioning
confidence: 97%
“…is considered an important fungal strain for the production of pectinase and is generally regarded as a safe (GRAS) microbe [13,14]. Many researchers have worked on the production of pectinase using different fungal strains such as Aspergillus fumigatus [15], Aspergillus oryzae [16], Aspergillus niger [17], Aspergillus tubingensis [18], Penicillium oxalicum [19], Penicillium chrysogenum [20], Fusarium proliferatum [21], Schizophyllum commune [22], Trichoderma harzianum [23], Geotricumcandidum [24], Rhizopus sp. [25], and Candida sp.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to our results, El-Shishtawy et al [54] reported repression of pectinase when glucose, lactose, maltose, and starch were used as sole carbon sources. A study in which orange peel was used as a carbon source reported the highest titer of pectinase [94].…”
Section: Effect Of Carbon Source and Nitrogen Sourcementioning
confidence: 99%
“…Govindaraji and Vuppu [67] reported orange peel as responsible for the highest pectinase activity (45.93 U/mL) with a novel strain, Streptomyces fumigatiscleroticus VIT-SP4, which supports the present findings. Ahmed and Awad [27] observed the highest pectinase activity (0.48 U/mL) for orange peels as the carbon source with Pencillium chrysogenum MF318506. Finally, Satapathy et al [23] found pectinase activity of 1366 ± 36.71 U/mL using Aspergillus parvisclerotigenus KX928754 with apple pomace as the carbon source.…”
Section: Effect Of Carbon Sourcesmentioning
confidence: 99%
“…Different microbial sources, such as fungi, yeasts, and bacteria, have been involved in the production of pectinases using solid-state fermentation (SSF) and submerged fermentation (SmF). Many researchers have worked on different fungal strains for pectinase production such as Aspergillus sojae [12,13], Aspergillus niger [14][15][16][17][18], Aspergillus fumigates [19,20], Aspergillus sydowii [10], Aspergillus tubingensis [21], Aspergillus carbonarius [22], Aspergillus parvisclerotigenus [23], Aspergillus oryzae [24], Penicillium oxalicum [25], Penicillium notatum and Coriolus versicolor [26], Penicillium chrysogenum [27], Fusarium proliferatum [28], Schizophyllum commune [29], Trichoderma harzianum [30], Rhizopus sp. [31], and Candida sp.…”
Section: Introductionmentioning
confidence: 99%